A novel method for secret image sharing Using nibble exchange - Chakraborty, Anirban; Das, Subhendu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper proposes a new scheme for secret image sharing which shuffles and manipulates the nibbles (and hence the bytes) of the pixel values of the images. We have developed a new algorithm called LDRU (Left-Down-Right-Up) for the construction of shares. Using LDRU algorithm any type of (Binary, Gray scale or Color) secret images can be shared and reconstructed precisely in linear time.